Program “PENAKUAT”: Pendampingan Menulis Kreatif Berbasis Mind Mapping untuk Meningkatkan Literasi Siswa UPT SPF SMP Negeri 21 Makassar - Alma Listiani; Muh. Destrian Al-Buchori; Nur Hikmah; Anita Candra Dewi (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2026)
Creative writing is an essential literacy competence that supports students’ academic achievement and communication skills. However, many junior high school students still experience difficulties in generating ideas, organizing writing structures, and producing coherent compositions. The PENAKUAT Program (Creative Writing Assistance Based on Mind Mapping) was implemented to improve students’ writing literacy at UPT SPF SMP Negeri 21 Makassar. This community service program aimed to enhance students’ creative writing skills, writing motivation, and classroom participation through the application of the mind mapping method. The program was conducted for four weeks involving 32 eighth-grade students using a participatory approach consisting of needs assessment, program socialization, mind mapping training, creative writing assistance, presentation, reflection, and evaluation. The evaluation employed pretest and posttest writing assessments, classroom activity observations, and student response questionnaires. The results indicated that the average writing score increased from 64.8 to 83.6. Improvements were found in idea development, text organization, vocabulary, language use, and writing mechanics. Furthermore, 90.6% of students actively participated in the activities, while 96.9% reported that the program significantly supported their writing process. The use of mind mapping enabled students to organize ideas visually, making the writing process easier, more systematic, and more creative. The program also improved students’ motivation and self-confidence in producing written work. Therefore, the PENAKUAT Program proved effective as an innovative writing literacy assistance model that strengthens school literacy culture and improves the quality of writing instruction in junior high schools.